Active exercise therapy improves the recovery of knee joint function and reduction of muscle atrophy after medial patellofemoral ligament reconstruction for recurrent patellar dislocation - Xing, Dong; Li, Wenyi; Yang, Zhaoxu; Dong, Zhijie; Kang, Huijun; Wang, Fei (Frontiers in Surgery, 2022)
Abstract Objectives: Medial patellofemoral ligament (MPFL) reconstruction is an important surgical therapy for recurrent patellar dislocation. However, few studies have focused on exercise therapy after MPFL reconstruction. Therefore, the first purpose was to compare the active and traditional postoperative exercise therapies on the recovery of knee joint function and reduction of muscle atrophy after MPFL reconstruction, and the second purpose was to compare the active and traditional postoperative exercise therapies on the patellar stability after MPFL reconstruction. Methods: The cases of 31 patients with recurrent patellar dislocation treated with patella double semi-tunnel anatomical MPFL reconstruction from February 2016 and February 2019 were retrospectively reviewed. The clinical outcomes, including the patellar tilt angle (PTA), lateral patellofemoral angle (LPFA), thigh circumference reduction, Kujala score, and Lysholm score, were compared between two groups (i.e., active exercise and traditional exercise groups) preoperatively, 3 months postoperatively, 6 months postoperatively, 12 months postoperatively, and 24 months postoperatively. Results: The Kujala score was significantly higher in the active exercise group than traditional exercise group 3 months postoperatively (80.06 versus 74.80, P<0.01), 6 months postoperatively (89.19 versus 82.07, P<0.01), 12 months postoperatively (91.43 versus 86.60, P<0.01), and 24 months postoperatively (92.50 versus 90.27, P=0.02). Similarly, there was a higher Lysholm score in the active exercise group compared with traditional exercise group 3 months postoperatively (81.25 versus 76.53, P<0.01), 6 months postoperatively (89.81 versus 84.80, P<0.01), 12 months postoperatively (93.25 versus 88.40, P<0.01), and 24 months postoperatively (93.69 versus 90.67, P<0.01). Significantly lower thigh circumference reduction was reported in the active exercise group compared with that in the traditional exercise group 3 months postoperatively (1.90 ± 0.57 versus 2.45 ± 0.45, P<0.01) and 6 months postoperatively (1.50 ± 0.31 versus 1.83 ± 0.32, P<0.01). No statistical difference was observed between the two groups in terms of PTA (P>0.05) or LPFA postoperatively (P>0.05). Conclusions: Our results suggested that active exercise therapy might benefit the early recovery of knee joint function and reduction of muscle atrophy in patients with recurrent patellar dislocation after MPFL reconstruction.